A Contrastive Analysis of the French and EmbSí Prepositions: The Case Study of ‘Dans’ and ‘Ts’ - Ndongo Ibara, Yvon-Pierre (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> This contribution focuses on the comparison of the syntactic and semantic analysis of the preposition with particular emphasis on the French preposition ‘dans’ and the Emb<span style="font-family: "Bookshelf Symbol 7"; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-char-type: symbol; mso-symbol-font-family: "Bookshelf Symbol 7"; mso-bidi-font-style: italic;" lang="EN-GB">Qsí ‘tsà’. It comes out from the discussion that the French preposition ‘dans’ substantiates the three semantic properties of preposition namely spatial, time and abstract features. Emb<span style="font-family: "Bookshelf Symbol 7"; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-char-type: symbol; mso-symbol-font-family: "Bookshelf Symbol 7"; mso-bidi-font-style: italic;" lang="EN-GB">Qsí ‘tsà’ on the contrary, instances two properties only notably spatial and time references. This analysis demonstrates that these two prepositions under discussion share the same syntactic distributions regarding their spatial and temporal properties. What distinguishes the two prepositions is the abstract and discursive property of ‘dans’ together with it collocations with number which is not attested in Emb<span style="font-family: "Bookshelf Symbol 7"; mso-ascii-font-family: Calibri; mso-ascii-theme-font: minor-latin; mso-hansi-font-family: Calibri; mso-hansi-theme-font: minor-latin; mso-ansi-language: EN-GB; mso-char-type: symbol; mso-symbol-font-family: "Bookshelf Symbol 7"; mso-bidi-font-style: italic;" lang="EN-GB">Qsí. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->